Truncation of exon 1 from the c-myc gene results in prolonged c-myc mRNa stability. - Rabbitts, P H (1985)
The human c-myc gene consists of three exons transcribed from two distinct promoters and the function of the first, noncoding exon is unknown. In COLO 320 cells, there co-exist normal and truncated (i.e., lacking exon 1) c-myc genes, both of which are transcribed. Studies on the turnover of c-myc mRNA show that the normal mRNA has an in vivo half-life of approximately 30 min which is approximately similar to the turnover time of the mRNA in lymphoblastoid cells. However, the truncated mRNA was found to be substantially more stable. This observation was also made with a Burkitt's lymphoma cell line which has a translocated, truncated c-myc gene. Therefore truncation of the c-myc gene can cause the mRNA to be more stable than the full size product suggesting that this can be a crucial factor in the activation of the c-myc oncogene, by exon 1 loss, in chromosomal translocation. The results also suggest a role for exon 1 in the c-myc mRNA degradative mechanism.